Opportunities to Educate Primary Class Students in Patriotic Spirit in New Textbooks - Koshmuradova Aziza; Korakhonova Oysara (Genius Journals, 2024)
In this article, the issues of increasing the sense of patriotism in new textbooks for primary school students are discussed and some concepts are presented.
Keywords: Motherland; young generation; independence